Priming of Brassica napus L. seeds with aqueous extract from mistletoe (Viscum album L.) boosts the content of photosynthetic pigments - Dąbrowska, Grażyna B.; Michalak, Magdalena; Antoszewski, Marcel; Kamiński, Dariusz; Mierek-Adamska, Agnieszka (Ecological Questions, 2024)
The increasing occurrence and severity of drought periods due to climate change have a negative impact on crop yield worldwide. In the face of a rising human population, this poses a severe threat to food security. Natural products such as plant extracts have many uses, but the studies about their potential usage in seed pre-sowing treatments have been limited. In this study, we evaluated the potential of Viscum album L. extract as a Brassica napus L. seed coating and seed priming agent. Moreover, its potential to limit the growth of commonly occurring foodborne pathogens was verified. The results showed that seed treatments with mistletoe macerate did not significantly affect hypocotyl and root length and biomass. Chlorophyll and carotenoid content of the plants treated with mistletoe extracts increased – with the best results obtained for the seeds humidified with 20% extract and 50% for priming. V. album extract exhibits weak antibacterial properties towards Escherichia coli and Salmonella typhimurium and does not show antibacterial properties against Staphylococcus aureus. This study points to the new possible use of plant extracts as an ecological way for seed pre-sowing treatment.